Comparative Evaluation of Extraction Methods on the Physicochemical Properties and Chemical Composition of Pistacia Lentiscus L. Oil - areibat, lila; Al-Kareiwi, Asma (AlQalam Journal of Medical and Applied Sciences, 2026)
This study explores the influence of three extraction techniques—hydrodistillation, cold pressing, and solvent maceration—on the physicochemical parameters and chemical composition of Pistacia lentiscus L. oil. The extracted oils were analyzed using gas chromatography with a flame ionization detector (GC-FID). The findings showed that, in comparison to the other extraction techniques, the cold-pressing approach produced higher density and refractive index values. The Brix value reached 69.3% for the cold-pressed sample, exceeding those produced via hydrodistillation and solvent maceration. GC-FID analysis identified six primary fatty acids in Pistacia lentiscus L. oil, with oleic acid (C18:1) being predominant—recording 48% in the cold-pressed oil, 45% in the hydrodistilled oil, and 32% in the alcoholic extraction. Thus, cold-pressing retained the most nutritious monounsaturated fatty acids. With measurements of 18% in the cold-pressed sample, 20% in the hydrodistilled sample, and 22% in the alcoholic extract, palmitic acid (C16:0) was the predominant saturated acid. This suggests that the use of organic solvents increases the number of saturated compounds. Linoleic acid (C18:2), a polyunsaturated fatty acid, revealed the largest percentage (16%) in the cold-pressed sample, compared with 13% and 8% for the hydrodistilled and alcoholic extracts, respectively. A balanced fatty acid profile was also found in trace levels of linolenic (C18:3), arachidic (C20:0), and stearic (C18:0) acids. These results highlight the advantages of cold pressing as a natural and effective way to maintain the nutritional integrity and quality of Pistacia lentiscus L. oil.